Effects of Cinnamon (Cinnamomum cassia) Consumption on Serum Lipid Profiles in Albino Rats - Alsoodeeri, Fahadah Naeef (J Lipids, 2020)
Dyslipidemia is an important cause of cardiovascular diseases (CVDs), which are the most prevalent causes of morbidity and mortality. The purpose of this study was to assess the effects of cinnamon on body weight gain, food intake, and serum lipid profiles of albino rats. This study was conducted on 30 healthy male albino rats weighing approximately 130 ± 5 g. The study was divided into the following two experiments: experiment (1), wherein rats were fed a laboratory diet; and experiment (2), wherein rats were fed a high-fat diet. In experiment 1, a total of 15 rats were divided into three groups. Group A (n = 5, untreated control) was fed laboratory diet, Group B (n = 5) was fed laboratory diet and cinnamon powder (2 g/kg body weight), and Group C (n = 5) was fed laboratory diet and cinnamon powder (4 g/kg body weight) for 30 days. In experiment (2), a total of 15 rats were similarly divided into three groups. Group D (n = 5, treated control) was fed laboratory diet plus high-fat diet, Group E (n = 5) was fed cinnamon powder (2 g/kg body weight) mixed with laboratory diet plus high-fat diet, and Group F (n = 5) was fed cinnamon powder (4 g/kg body weight) mixed with laboratory diet plus high-fat diet daily for 30 days. An administration of 4 g/kg body weight of cinnamon extract powder decreased the final weight by 4.4%, body weight gains by 31.41%, food intake by 1.7%, and food efficiency ratio by 22.38% in hypercholesterolemic adult male rats as well as serum total cholesterol by 31.22%, triglyceride by 24.05%, and LDL-C by 43.49%, with an increase in the levels of HDL-C by 30.16%, furthermore, a significant decrease in serum total cholesterol, triglycerides, and LDL-C levels and increasing serum HDL-C on day 30 were observed (P < 0.001). This finding provides scientific evidence to substantiate the traditional use of cinnamon to treat hyperlipidemia.